For better or for worse: does the UK means-tested social security system encourage partnership dissolution?. (1st February 2020) - Griffiths, Rita
Abstract : Unemployed and low-income couples entitled to means-tested benefits are known to have higher rates of separation and divorce than couples in which one or both partners are in regular, paid work. However, how and why unemployment and benefit receipt increases the risk of partnership dissolution remains the subject of much debate. In recent policy discourse, financial differentials in benefit entitlement between lone and couple parents are said to encourage intact couples to separate. Based on in-depth, face-to-face interviews with a group of low-income mothers who had been partnered prior to claiming lone parent benefits, this paper explores whether benefit entitlement or receipt influenced the decision to separate or divorce. The research found that more salient to partnership dissolution than the amount of benefits a couple may have been entitled to, was who had access to the money, how it was managed and how it was spent. To the extent that welfare systems influence which member of a couple has access to household income, the design and administration of benefits was having an important contributory effect. Policy implications of paying Universal Credit to couples in the form of a single monthly household award into one bank account are discussed.